Simultaneous multi-product sterilization: Revisited, explored, and optimized. (January 2019) - Simpson, R.; Ramirez, C.; Jiménez, D.; Almonacid, S.; Nuñez, H.; Angulo, A.
Abstract: An interesting potential improvement and challenge in thermal processing of packaged foods is the implementation of simultaneous multi-product sterilization. The aim of this research was to analyze, explore, and optimize simultaneous multi-product sterilization through thermal processing simulation of packaged foods considering both constant (CRT) and variable retort temperature (VRT) profiles. The research was approached through three main tasks, which were defined to discover potential opportunities for simultaneous multi-product sterilization with the attempt to recommend the steps to follow to practically implement it. In most cases, simultaneous multi-product sterilization for CRT processing was feasible, however, it was limited to low retort temperature and restricted to products with similar fh. In contrast, in VRT profiles a higher flexibility for simultaneous multi-product sterilization was found. The opportunity to carry out simultaneous multi-product sterilization provides flexibility to optimize retort utilization, reduce energy consumption, and increase processing plant productivity. Highlights: Simultaneous multi-product sterilization improves processing plant productivity. Variable retort profiles reduce processing time in multi-product sterilization.W. Variable retort profiles expands the opportunities of multi-product sterilization. Simultaneous processing could be extended to processes such as drying and freezing.